Hubungan Umur, pH, dan C-Organik Terhadap Kerusakan Eucalyptus sp Akibat Serangan Angin: The Relationship of Age, pH, and C-Organic to Eucalyptus sp Wind Damage - Suhartati, Tatik; Maystang, Jeffry; Kusumaningsih, Karti Rahayu; Purwadi, Purwadi (HUTAN TROPIKA, 2024)
The planting process of Eucalyptus sp is susceptible to wind damage. Many factors cause trees to be damaged by wind. These factors include the condition of the stand and other factors. This study aims to determine the relationship between stand age, soil characteristics (pH and C-Organic) to the percentage of wind damage. A total of 179 permanent plots were sampled at three ages of 6, 18 and 30 months. Multiple linear regression backward elimination method was used to determine the relationship of age, pH and C-organic to the percentage of damage. The results showed that the older the age of the stand, the percentage of damage increased. Soil characteristics have not been able to explain their direct.